The dangerous "West Coast Swing" by hyperglycaemia and chronic stress in the mouse hippocampus: Role of kynurenine catabolism - Micaela Gliozzi; Anna Rita Coppoletta; Antonio Cardamone; Vincenzo Musolino; Cristina Carresi; Saverio Nucera; Stefano Ruga; Federica Scarano; Francesca Bosco; Lorenza Guarnieri; Roberta Macrì; Rocco Mollace; et al. (Elsevier, 2024)
Growing epidemiological studies highlight a bi-directional relationship between depressive symptoms and diabetes mellitus. However, the detrimental impact of their co-existence on mental health suggests the need to treat this comorbidity as a separate entity rather than the two different pathologies. Herein, we characterized the peculiar mechanisms activated in mouse hippocampus from the concurrent development of hyperglycaemia, characterizing the different diabetes subtypes, and chronic stress, recognized as a possible factor predisposing to major depression. Our work demonstrates that kynurenine overproduction, leading to apoptosis in the hippocampus, is triggered in a different way depending on hyperglycaemia or chronic stress. Indeed, in the former, kynurenine appears produced by infiltered macrophages whereas, in the latter, peripheral kynurenine preferentially promotes resident microglia activation. In this scenario, QA, derived from kynurenine catabolism, appears a key mediator causing glutamatergic synapse dysfunction and apoptosis, thus contributing to brain atrophy. We demonstrated that the coexistence of hyperglycaemia and chronic stress worsened hippocampal damage through alternative mechanisms, such as GLUT-4 and BDNF down-expression, denoting mitochondrial dysfunction and apoptosis on one hand and evoking the compromission of neurogenesis on the other. Overall, in the degeneration of neurovascular unit, hyperglycaemia and chronic stress interacted each other as the partners of a "West Coast Swing" in which the leading role can be assumed alternatively by each partner of the dance. The comprehension of these mechanisms can open novel perspectives in the management of diabetic/depressed patients, but also in the understanding the pathogenesis of other neurodegenerative disease characterized by the compromission of hippocampal function.